Golden Horde Settlements of the North-Eastern Caspian Region: geography, topography, housing construction - Sagidullaev Daryn Z. (Поволжская археология, 2022)
The article considers the features of the formation of the settlement structure of the Golden Horde period in the area of the Ural River basin in the north-east of the Caspian Sea. The archaeological sites located on the banks of the Ural River of this era include the settlements: Saraychik, Zhaiyk, Zhalpaktal and Aktobe-Laeti. Based on the materials of archaeological research, the geographical characteristics of the region, the historical topography of their location and the peculiarity of the planography of urban development are analyzed. The materials of the addition of the urban settlements of the Golden Horde on the Ural River are presented, as well as the historical topography of the settlements and the features of housing construction are reconstructed.